2018
DOI: 10.1080/15438627.2018.1447474
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography and clinical examination of knee injuries in pre- and post- menarche dancers

Abstract: This study aimed at evaluating whether the prevalence of knee injuries and morphological features are different among pre-and-post menarche dancers; Sixty-seven pre-and-post menarche dancers were screened for anthropometric parameters; knee laxity; patella femoral pain syndrome (PFPS), pathologies and anatomical structure of the knees. Both groups showed a high and similar prevalence of PFPS. The post-menarche dancers produced a significantly higher rate of Tanner stages 3-4 (p = .010), greater weight (p < .00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…4 Other studies have supported the capabilities for ultrasonography to predict development of symptoms in patellar tendons of soccer and volleyball players, as well as ballet dancers. 3,6,8,20,21 While numerous studies have assessed ultrasonography of quadriceps tendons as a prescreening tool for injury risk, the present study was the first to document its effectiveness in determining risk for noncontact quadriceps muscle disorders. Total 132…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…4 Other studies have supported the capabilities for ultrasonography to predict development of symptoms in patellar tendons of soccer and volleyball players, as well as ballet dancers. 3,6,8,20,21 While numerous studies have assessed ultrasonography of quadriceps tendons as a prescreening tool for injury risk, the present study was the first to document its effectiveness in determining risk for noncontact quadriceps muscle disorders. Total 132…”
Section: Discussionmentioning
confidence: 89%
“…Comin et al and Visnes et al reported ultrasonography of the quadriceps and patellar tendons of athletes to be effective in determining relative risk for tendon-related injuries. 3,9 Furthermore, there are other studies that document strong correlations between abnormal ultrasonographic findings and development or worsening of patellar tendinopathy in basketball, 4 soccer, 6,20 and volleyball players, 8 as well as ballet dancers 3,21 and fencers. 7 As such, ultrasonography of the knee has the potential to serve as an effective screening tool for determining risk for common noncontact knee injuries sustained by American football players in an effort toward reducing injury risk through education, screening, prevention, and training programs aimed at the factors identified.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The rationale for measuring only patellofemoral pain (PFP) among our dancers in the current study (regardless of other conditions) was that GJH and scoliosis were reported to be related to PFP [24]. Furthermore, PFP was found to be the most prevalent musculoskeletal condition among young adolescent dancers along the growthspurt period [25]. In addition, young dancers suffering from PFP were found to have a significantly greater prevalence of scoliosis, a higher prevalence of hypermobility of the patella in knee extension and a higher prevalence of hypermobility of the patella in 30°knee flexion compared with dancers with no-PFP [26].…”
Section: Introductionmentioning
confidence: 94%
“…GJH was assessed by the Beighton 9-Point Hypermobility Test, following previous publications [25,31]. A dancer was diagnosed with GJH if she had a Beighton score of ≥5/9 [25,31].…”
Section: Generalized Joint Hypermobility (Gjh)mentioning
confidence: 99%